Boron clusters with 46, 48, and 50 atoms: competition among the core–shell, bilayer and quasi-planar structures. Issue 37 (29th June 2017) - Sai, Linwei; Wu, Xue; Gao, Nan; Zhao, Jijun; King, R. Bruce
Abstract : Using a genetic algorithm combined with density functional theory calculations, we perform a global search for the lowest-energy structures of B n clusters with n = 46, 48, 50. Abstract : Using a genetic algorithm combined with density functional theory calculations, we perform a global search for the lowest-energy structures of B n clusters with n = 46, 48, 50. Competition among different structural motifs including a hollow cage, core–shell, bilayer, and quasi-planar, is investigated. For B46, a core–shell B4 @B42 structure resembling the larger B n clusters with n ≥ 68 is found to compete with a quasi-planar structure with a central hexagonal hole. A quasi-planar configuration with two connected hexagonal holes is most favorable for B50 . More interestingly, an unprecedented bilayer structure is unveiled at B48, which can be extended to a two-dimensional bilayer phase exhibiting appreciable stability. Our results suggest alternatives to the cage motif as lower-energy B n cluster structures with n > 50.